Propuesta de mejoramiento en la logística de almacenamiento y manejo de materiales para el área de mantenimiento de la línea de formado en Tenaris Tubocaribe (2021)
The company Tenaris Tubocaribe is a multinational with great international recognition and whose owned as majority Group is: Argentino Techint, was founded in 2001 in Campana Argentina and currently has 26,980 and more than 25 offices in the world. One such branch It is located in Cartagena de Indias, being the only one in the country. In the Bolivarian capital located in the Carlos Vélez Pombo Industrial Park; km 1 road to Turbaco, has a annual production capacity close to 198,000 tons of its most representative products such as: seamless and seamless steel tubes. Regarding the productive situation, this organization shows several problems, one of the determining factors when analyzing its productivity and competitive is the storage, review of merchandise, supplies and especially of the errors of the systematization, categorization and homogenization processes of the spare parts for the maintenance of the different equipment used in the forming line. Inside one of the causes is the inefficiency of the organization process in the reception and storage, so the consequences are notable in the economic and labor plane. In In view of this situation, this organization was allowed access to evaluate said section of storages, and therefore an investigative objective was reached such as DESIGN OF A SPARE PARTS RECEPTION AND STORAGE SYSTEM, supported by the diagnosis of the spare parts warehouse facilities for the maintenance of the different equipment used in the forming line. All this in terms of reception and storage, thus determining to guarantee the most optimal flow in the supply chain. For this, a description of the existing situation, specifically the problem, was made in the which will describe the current situation of the reception, categorization, detailed, systematization and storage of the spare parts stored in the main warehouse.